Stomp the Yard - Makomborero, Violet (WritingThreeSixty, 2025)
No longer shall you make hollow spaces like snow angels within your mattress of your bed. Get up! Get out! Stomp the yard! – the whole nine yards Leave no inch unclaimed. The world needs you.